2020
DOI: 10.3389/fcell.2020.606123
|View full text |Cite
|
Sign up to set email alerts
|

EGCG Enhanced the Anti-tumor Effect of Doxorubicine in Bladder Cancer via NF-κB/MDM2/p53 Pathway

Abstract: Doxorubicin (DOX), the first-line chemotherapy for bladder cancer, usually induces side effects. We previously demonstrated that green tea polyphenol EGCG had potent anti-tumor effect in bladder cancer via down regulation of NF-κB. This study aimed to investigate the additive/synergistic effect EGCG and DOX against bladder cancer. Our results demonstrated that the combined use of DOX and EGCG inhibited T24 and SW780 cell proliferation. EGCG enhanced the apoptosis induction effect of DOX in both SW780 and T24 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Therefore, there is an urgent need to develop new treatments for CRC. EGCG is the most biologically active polyphenol in green tea and takes on multiple roles in cancer prevention and treatment [10] . A previous study clarifies EGCG induces CRC cell apoptosis by inducing endoplasmic reticulum stress through the Protein Kinase RNA-Like Endoplasmic Reticulum Kinase (PERK)/ phosphorylated eukaryotic translation Initiation Factor 2 Alpha (p-eIF2α)/Activating Transcription Factor 4 (ATF4) and Inositol-Requiring Enzyme 1 α (IRE1α) pathways [23] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there is an urgent need to develop new treatments for CRC. EGCG is the most biologically active polyphenol in green tea and takes on multiple roles in cancer prevention and treatment [10] . A previous study clarifies EGCG induces CRC cell apoptosis by inducing endoplasmic reticulum stress through the Protein Kinase RNA-Like Endoplasmic Reticulum Kinase (PERK)/ phosphorylated eukaryotic translation Initiation Factor 2 Alpha (p-eIF2α)/Activating Transcription Factor 4 (ATF4) and Inositol-Requiring Enzyme 1 α (IRE1α) pathways [23] .…”
Section: Resultsmentioning
confidence: 99%
“…For example, in Breast Cancer (BC), EGCG refrains cell proliferation and differentiation, induces apoptosis and targets angiogenesis by depressing Vascular Endothelial Growth Factor (VEGF) transcription [9] . In bladder cancer, EGCG enhances the sensitivity of bladder cancer cells to the chemotherapeutic drug doxorubicin [10] . Meanwhile, EGCG enhances the sensitivity of CRC cells to the cancer chemotherapeutic drug 5-FU by restraining the Glucose Regulated Protein 78 (GRP78)/ Nuclear Factor Kappa B (NF-κB)/micro Ribonucleic Acid (miR)-155-5p/Multidrug Resistance Protein 1 (MDR1) pathway [11] .…”
mentioning
confidence: 99%
“…Multiple molecules could enhance bladder cancer cell migration, invasion, and proliferation by activating NF- κ B signaling [ 27 , 28 ]. Some compounds can also inhibit bladder cancer by inhibiting NF-kappa B [ 25 , 26 , 29 ]. This study shows that quercetin is the most studied monomer compound in all traditional Chinese medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenol quercetin is another anticancer compound that works synergistically with paclitaxel ( 349 , 350 ), tamoxifen ( 351 ), cisplatin ( 352 , 353 ), adriamycin ( 354 ), and gemcitabine ( 355 ) to suppress the growth of various models of cancer via enhanced ROS production, cell cycle arrest, ER stress, and apoptosis. Similarly, various studies have reported the advantages of adding EGCG to enhance the antitumor activity of sunitinib, irinotecan, doxorubicin, gemcitabine, and cisplatin against human lung (A549, H460, and H1975) ( 356 , 357 ), colorectal (HCT116 and RKO) ( 358 ), bladder (SW780 and T24) ( 359 ), pancreatic (MIA PaCa-2 and Panc-1) ( 360 ), and ovarian (OVCAR3 and SKOV3) ( 361 ) cancer cells, respectively. The results emphasized that EGCG could potentate the antineoplastic activity of the aforementioned drugs by increasing the sensitivity of the cancer cells, thereby enhancing their antiproliferative activity, damaging DNA, interfering with the NF-κB/MDM2/p53 pathway, inhibiting Akt, and elevating copper transporter 1 (CTR1).…”
Section: Phytochemicals In Combination With Anticancer Drugs Potentia...mentioning
confidence: 99%